2023
DOI: 10.3389/fpsyt.2023.1154354
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive transcranial alternating current stimulation for patients with major depressive disorder: A systematic review and meta-analysis

Abstract: ObjectiveWe performed a meta-analysis of randomized, double-blind, controlled trials (RCTs) to systematically investigate the therapeutic effects and tolerability of transcranial alternating current stimulation (tACS) for the treatment of patients with major depressive disorder (MDD).MethodsElectronic search of PubMed, PsycINFO, EMBASE, Chinese National Knowledge Infrastructure, Wanfang database, and the Cochrane Library up to 1 April 2022. Double-blind RCTs examining the efficacy and safety of tACS for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The findings from this meta-analysis suggest that tACS could be a viable non-pharmacological intervention for individuals with schizophrenia. Beyond its effectiveness in improving total and negative psychopathology of schizophrenia, tACS has been explored as a treatment for major depression (MDD) ( 45 ), chronic insomnia ( 46 ), attention deficit hyperactivity disorder (ADHD) ( 47 ), and pain disorders ( 48 ). For instance, a recent meta-analysis has determined that tACS effectively alleviates depression symptoms in individuals with MDD ( 45 ) while ensuring safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from this meta-analysis suggest that tACS could be a viable non-pharmacological intervention for individuals with schizophrenia. Beyond its effectiveness in improving total and negative psychopathology of schizophrenia, tACS has been explored as a treatment for major depression (MDD) ( 45 ), chronic insomnia ( 46 ), attention deficit hyperactivity disorder (ADHD) ( 47 ), and pain disorders ( 48 ). For instance, a recent meta-analysis has determined that tACS effectively alleviates depression symptoms in individuals with MDD ( 45 ) while ensuring safety.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its effectiveness in improving total and negative psychopathology of schizophrenia, tACS has been explored as a treatment for major depression (MDD) ( 45 ), chronic insomnia ( 46 ), attention deficit hyperactivity disorder (ADHD) ( 47 ), and pain disorders ( 48 ). For instance, a recent meta-analysis has determined that tACS effectively alleviates depression symptoms in individuals with MDD ( 45 ) while ensuring safety. Furthermore, a systematic review of RCTs ( n = 73) has demonstrated tACS as an effective and safe therapeutic approach for chronic insomnia ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive brain stimulation techniques, such as transcranial magnetic stimulation (TMS) ( 10 ), transcranial direct current stimulation (tDCS) ( 11 ), and transcranial alternating current stimulation (tACS) ( 12 ), provide a nonpharmacological alternative for MDD. High-frequency (≥ 5 Hz) repetitive transcranial magnetic stimulation (HF-rTMS) was approved by the Food and Drug Administration (FDA) as a noninvasive brain stimulation technique for TRD in 2008 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a real-world study found a significant reduction of depressive symptoms in patients suffering from TRD after receiving esketamine nasal spray (5). Apart from antidepressant medication, strategies such as vagus nerve stimulation (6), electroconvulsive therapy (7,8), transcranial alternating current stimulation (9), and transcranial magnetic stimulation (TMS) [e.g., deep TMS (10), accelerated TMS (11), intermittent theta-burst stimulation (iTBS) (12), accelerated iTBS (13), bilateral TBS (14), and continuation TBS (15)], have been developed as a nonpharmacological alternative for the treatment of MDD.…”
Section: Introductionmentioning
confidence: 99%